ESTIMATING BODY COMPOSITION IN BIOIMPEDANCE: A STUDY WITH THE POLICE CIA SHOCK MILITARY POLICE PIAUÍ (Fiep Bulletin - online, 2016)
Introduction: Body composition is one of the components of physical fitness and interferes directly or indirectly in overall fitness. It is believed that officers who submit the best level of body composition may also show better performance in other items of physical fitness. Objective: To assess body composition by bioimpedance technique and physical fitness components of the Company's officers Shock Battalion Rounds Chichi Special Natures (BPRONE) of the Military Police of Piauí. Methodology: The survey was characterized as a field study of quantitative and descriptive transversal character. The study was conducted in the city of Teresina-Pi in the period January to July 2014, with the initial sample 31 police officers, male, aged between 20 and 39 years of Cia Shock BPRONE the Military Police of Piauí. Results: The mean for age was 31.1 years; working time within the police was 7.2 years and time in CIA shock of 19 months; Body weight and height were 81.54 kg and 1.75 meters. The fat percentage was 27.74%; liquid tissue (LT%) presented with the average 50.78%. Muscle mass (MM%) of the population studied showed an average of 40.59% and bone mass (BM%) with 3.07%. Conclusion: It is concluded that the officers of the Company shock BPRONE Military Police of Piauí meet with the percentage of fat above the desired range. The values ??of liquid tissues, bone and muscle are within the appropriate cut-off point. Although not discussed because they have not published studies on the subject and the method of bioimpedance.
Keywords: Body composition; military police; bioimpedance